Front Cover. Issue 7 (July 2017) - Ramos, Raül; Carlile, Nicholas; Madeiros, Jeremy; Ramírez, Iván; Paiva, Vitor H.; Dinis, Herculano A.; Zino, Francis; Biscoito, Manuel; Leal, Gustavo R.; Bugoni, Leandro; Jodice, Patrick G. R.; Ryan, Peter G.; et al.
Abstract : The cover image, by Raül Ramos et al ., is based on the Biodiversity Research It is the time for oceanic seabirds: Tracking year‐round distribution of gadfly petrels across the Atlantic Ocean, DOI:10.1111/ddi.12569 . Photo Credit: Jacob González‐Solís.